Nature and prevalence of adverse drug reaction of antiretroviral medications in Halibet National Referral Hospital: a retrospective study - Lidya Hagos; Siyoma Fessehaye; Indermeet Singh Anand (BMC, 2019)
Abstract Background Monitoring the safety of antiretroviral therapy (ART) remains a challenge in resource-constrained countries such as Eritrea due to their serious adverse drug reactions (ADRs). This study was aimed at assessing the prevalence, nature, seriousness and possible risk factors of ART associated ADRs in Halibet National Referral Hospital in Eritrea. Method A three month retrospective, longitudinal, descriptive study of patients treated with ART between September 2005 and December 2016 was conducted in Halibet National Referral Hospital. Demographic characteristics, treatment details, reaction and outcome details, laboratory investigations and other information was abstracted manually from patients' clinical cards. Statistical analysis was conducted using both univariate and multivariate analysis and statistical significance was tested using 95% confidence intervals and/or p-value. A P-value < 0.05 was regarded as being statistically significant. Results Of the 309 patients screened, 62.8% encountered at least one ADR and 29.8% of the reactions were serious with similar male to female ratio. Gastrointestinal symptoms were the most common ADR and were associated mostly with Atripla followed by AZT + 3TC + NVP drug combinations, but lipodystrophy followed by peripheral neuropathy which were both commonly associated with Stavudine and anemia associated with Zidovudine were the most serious. Patients with CD4 count below 200 were more likely to develop ADRs (p = 0.000). Conclusion ADRs associated with ART drugs in Halibet hospital were found to be highly prevalent. Furthermore, CD4 count below 200, was identified as a major risk factor that predisposes patients to ADRs. This is burdensome to resource constrained countries such as Eritrea who have limited drug options and high HIV prevalence, therefore these findings will help patients and healthcare professionals understand the nature as well as seriousness of these ADRs and identify the risks involved with ART medications which can help minimize ART associated ADRs early on.